2015
DOI: 10.1108/apjba-09-2014-0112
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of antecedents and consequences of brand love in India

Abstract: Purpose – The purpose of this paper is to explore the factors that drive consumer love toward a brand and the opportunities a consumer’s love create for a brand in India. Design/methodology/approach – A total of 23 in-depth interviews were conducted with consumers. The interview transcripts were analyzed through thematic analysis using qualitative software Nvivo10. Findings – This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 94 publications
3
46
0
Order By: Relevance
“…Our research has shown similar findings that a brand's reputation and brand experience are positively related with brand love and brand love is subsequently associated with eWOM in Smartphone industry. These results are consistent with the previous research conducted in other sectors (Garg et al, 2015; Karjaluoto et al, 2016; Unal & Aydın, 2013). Our research therefore fills the gap in identifying the relationship between a brand reputation and brand experience with brand love and with eWOM in Smartphone industry in Pakistan.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our research has shown similar findings that a brand's reputation and brand experience are positively related with brand love and brand love is subsequently associated with eWOM in Smartphone industry. These results are consistent with the previous research conducted in other sectors (Garg et al, 2015; Karjaluoto et al, 2016; Unal & Aydın, 2013). Our research therefore fills the gap in identifying the relationship between a brand reputation and brand experience with brand love and with eWOM in Smartphone industry in Pakistan.…”
Section: Discussionsupporting
confidence: 93%
“…The concept of brand love is in an infancy stage. The effect of self‐expressiveness, brand trust, and hedonic value on brand love have been studied in previous research (Albert & Merunka, 2013; Carroll & Ahuvia, 2006), yet the past research suggests that there is a need for further investigation on brand experience as an antecedent of brand love (Garg, Mukherjee, Biswas, & Kataria, 2015). Moreover, in previous studies, there was not any significant relationship found between brand love and eWOM (Karjaluoto, Munnukka, & Kiuru, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another hypothesis of the research is the H2 hypothesis, which claims that the brand experience positively affects brand love. The positive effect of brand experience on brand love was determined in the literature in various studies (Roy et al, 2013, p. 330;Garg et al, 2015, Garg, Mukherjee, Biswas andKataria, 2016;Pandowo, 2016;Erdoğan and Enginkaya, 2018;Zhang, 2019). Rodrigues et al (2007) determined in their research that brand experience in online shopping has no positive effect on brand love.…”
Section: Conclusion and Recommendationsmentioning
confidence: 98%
“…In the study, the participants were asked to answer the questionnaire questions by stating a brand name that they thought was special for them and that they had experienced for many years without naming any product category or sector. This approach was used in similar studies in the literature (Baycur, 2015, p. 15;Garg et al, 2015;Uyar and Lekesizcan, 2017). Thus, in evaluating experiences with a private brand, the cumulative brand experiences created by sensory, emotional, intellectual and behavioral experiences based on stimuli related to a brand can be evaluated together (van der Westhuizen, 2018, p.174).…”
Section: Demographic Characteristics Of Participants and Findings Regarding The Brands Indicatedmentioning
confidence: 99%
See 1 more Smart Citation